Single and loving it A study on the happiness of being single. - Bertis, Antonette A.; Calixtro, Marihden L.; Torrevillas, Jewelyn M. (Tacloban City Antonette A. Bertis, Marihden L. Calixtro [and] Jewelyn M. Torrevillas, 2010)
"Single and Loving It: A Study on the Happiness of Being Single" is a qualitative study on the life of single women in Tacloban City and Naval, Biliran. These sixteen (16) single women ages 40 years old and above were identified through purposive sampling, in which an interview schedule was utilized by the researchers. The study is aimed on finding out if singlehood provides a situation conducive to human growth, self-fulfillment, and happiness. Results indicated that singlehood entails problems, difficulties, and even subtle discrimination from the society. But this does not hinder them from achieving personal growth, happiness, and life satisfaction. With the help of this study, the society will recognize that being single does not signify that a woman could hardly be happy or fulfilled in life.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science